2010
DOI: 10.1007/s11912-010-0134-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy for Cervical Cancer in 2010

Abstract: The introduction of concurrent chemotherapy and radiotherapy for the definitive treatment of cervical cancer constituted a major advance in the management of cervical cancer, resulting in a significant improvement in local control, progression-free survival, and overall survival. Since the publication of the results of seminal trials demonstrating the benefits of platinum-based chemotherapy, investigations of new cytotoxic and targeting agents have continued. The success of these studies has been limited in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 71 publications
1
20
0
Order By: Relevance
“…HT can often limit the ability to deliver a full course of concurrent chemotherapy and is a major limitation to the introduction of additional cytotoxic agents (13). IMRT treatment planning for intact cervical cancer requires large margins on the cervix, perhaps on the order of several centimeters, to allow for uterine motion (14).…”
Section: Discussionmentioning
confidence: 99%
“…HT can often limit the ability to deliver a full course of concurrent chemotherapy and is a major limitation to the introduction of additional cytotoxic agents (13). IMRT treatment planning for intact cervical cancer requires large margins on the cervix, perhaps on the order of several centimeters, to allow for uterine motion (14).…”
Section: Discussionmentioning
confidence: 99%
“…MRI-guided brachytherapy with the addition of interstitial needles has shown promise in improving local control [24]. New approaches to combining radiotherapy with chemotherapy or new molecular therapeutics targeted at radioresistance pathways [25] are needed to address the problem of distant relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer rates are decreasing among women in the United States, although incidence remains high among Hispanic/Latino, Black, and Asian women (Barnholtz-Sloan et al, 2009). Radiotherapy is the primary modality for curative treatment of locally advanced cervical cancer (Klopp et al, 2011). Several randomized trials revealed that treatment regimens combining radiotherapy with platinum-based chemotherapy improve rates of overall survival and progress-free survival in women with Stage ⅢB through ⅣA cervical cancer (Rose et al, 1999;Eifel et al, 2004;Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%